Children’s Learning From Interactive eBooks: Simple Irrelevant Features Are Not Necessarily Worse Than Relevant Ones - Etta, Roxanne A.; Kirkorian, Heather L. (Frontiers in Psychology, 2019)
The purpose of this study was to investigate experimentally the extent to which children’s novel word learning and story comprehension from eBooks depends on the relevance of interactive eBook features. A story was created in the lab to incorporate novel word-object pairs. The story was read to preschoolers (3-5 years old, N = 103) using one of the three books: noninteractive control, interactive-relevant, interactive-irrelevant. Novel word learning and story comprehension were assessed with posttests in which children picked target objects from an array and sorted story events into sequences, respectively. Findings indicate that word learning and story comprehension were similar across all three books, suggesting that simple interactive features – whether relevant or irrelevant to the story – had little impact on learning in this controlled experiment.